Constructions Project Management Risks’ Framework - Ansah, Richard Hannis; Sorooshian, Shahryar; Shariman, Mustafa; Oluyinka, Oludapo Samson (Romanian Society for Quality Assurance - SRAC, 2017)
The characteristic and inherent risks in construction projects present key difficulties to stakeholders and project teams. Risk appraisal is a significant step toward potential variables identification and evaluation. In risk assessment, adequate categorization and prioritization aid planning, budgeting and management of project related risks. In this paper, an analysis of the risks associated with the delay sources in the internal environment of Malaysian construction projects have been presented based on risk priority number (RPN) to determine the degree of severity, occurrence and detection. Through literature review, eighty one risks under four main delay sources were extracted for further analysis. From the results, the main risks include contractor’s financial problems, poor coordination by the contractor, change orders, client’s financial problems, errors and defective work, poor materials management, poor communication between consultant and contractor, unrealistic contract duration, poor procurement tools and methods, unavailability of materials and labors, ineffective coordination by project managers, poor construction site layout, changes in material types and specification, inaccuracies in estimation and budgeting, delays in approvals, respectively. This study would provide a decision tool for prioritizing and categorizing risks in construction projects to build a realistic and rational resources allocation guide.